Tinjauan Sistematis: Peran Inovasi Teknologi dalam Meningkatkan Kepuasan Masyarakat terhadap Pelayanan Publik - Rista Ningsih; Salma Afal Alshadiqa; Rina Wahyuni; Jumiati Jumiati; Boni Saputra (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to examine the influence of technological innovation on public satisfaction in public service delivery through a literature review approach. In the digital era, the use of technologies such as e-government and e-services has become a key strategy to enhance efficiency, transparency, and service quality. Based on the analysis of five relevant journal articles, three showed effective implementation of digital technology, resulting in improved public satisfaction. However, two journals revealed suboptimal outcomes due to obstacles such as limited infrastructure, low digital literacy, and insufficient socialization. These findings suggest that the success of technological innovation in public services highly depends on technical readiness, policy support, and the public’s ability to utilize digital services.